Pengaruh Lingkungan Kerja Terhadap Kinerja Melalui Kepuasaan Kerja Pada PT. Bank Artha Graha Tbk. Pekanbaru - Wiwin Cristi Amelia; Samsir '; Marzolina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to identify and analyze the influence of the work environment on the performance of the company through employee job satisfaction in PT. Bank Artha Graha Tbk Pekanbaru, to determine the effect of work environment on job satisfaction in PT. Bank Artha Graha Tbk Pekanbaru, and to determine the effect of work environment on performance in PT. Bank Artha Graha Tbk Pekanbaru. The sampling method using a sample using random sampling techniques, namely the sampling techniques that provide equal opportunities to the members of the population to be able to become members of the sample. Determination of the number of samples is done by using the formula in Riduwan Slovin (2005:65). From the calculations, the number of samples as many as 52 employees at PT. Bank Artha Graha Tbk Pekanbaru. Data collection methods used observations are researchers involved with the everyday person being observed or used as a source of research data, the questionnaire was carried out data collection techniques of data by compiling a list of questions and then pass it to the respondents in the study, and this documentation techniques used to obtain data from the company, especially knowing the state of the company. Data were analyzed using descriptive statistics to describe the use of data each variable, testing the quality of data, and path analysis.The results showed that the relationship between work environment on performance through employee job satisfaction in PT. Bank Artha Graha Tbk Pekanbaru is very strong at (r = 0.083). The coefficient of determination or R-square is a figure of -, 007. For multiple linear regression should use the adjusted R square Adjusted R square or written, as adjusted by the number of independent variables were used, whereby if the independent variable 1 (one) then use the R-square and if it exceeds 1 (one) using the adjusted R square . Adjusted R square is equal to - .034 this means that 64.4% of the variation in the dependent variable of performance and job satisfaction of employees at PT. Bank Artha Graha Tbk Pekanbaru which can be explained by the independent variables work environment while the rest is explained by other variables.Keywords: Work Environment, Performance and Job Satisfaction